Multi-layer composite waterproof and explosion-proof corrugated paperboard and preparation method thereof

Through the design of multi-layer composite structure and green flame retardant adhesive, corrugated cardboard is solved, and the problem of insufficient waterproofness and flame retardancy under strong impact is achieved, achieving higher resistance to deformation, explosion and flame retardancy. performance.

CN118814526BActive Publication Date: 2025-02-18南京鑫瑞包装有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410935180.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-02-18
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

Existing corrugated cardboard is prone to rupture under strong external impact, and has insufficient waterproofness and flame retardancy, making it difficult to use in humid, high temperature or open flame environments.

Method used

Using a multi-layer composite structure, the explosion-proof membrane layer, foam board layer, reinforced fiber mesh layer and corrugated cardboard layer are used as flame retardant adhesives by modifying Elosite nanotubes, composite water-based polyurethane and cross-linked oxidized starch composite as flame retardant adhesives. The protective layer is formed by bonding in turn, and the modified Elosite nanotubes and composite water-based polyurethane are combined as protective coatings.

Benefits of technology

Improves the deformation resistance, explosion-proof and flame-retardant properties of corrugated cardboard, and enhances its service life and safety in humid, high temperature or open flame environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of paperboard, in particular to a multi-layer composite waterproof and explosion-proof corrugated paperboard and a preparation method thereof. An explosion-proof film layer, a foam board layer, a reinforcing fiber mesh layer and a corrugated paperboard layer are sequentially bonded with a green flame-retardant adhesive to obtain a corrugated paperboard, and a modified halloysite nanotube and a composite waterborne polyurethane are compounded as a protective coating to be coated on the corrugated paperboard; cross-linked oxidized starch is compounded with the composite waterborne polyurethane and the modified halloysite nanotube to obtain a flame-retardant adhesive; the halloysite nanotube is modified by firstly amminating its surface with 3-aminopropyltriethoxysilane, and then graphene oxide is loaded on its surface by electrostatic self-assembly to obtain a hybrid flame-retardant filler, namely, a composite halloysite nanotube, which is then modified with aspartic acid and then reactively grafted with a salicylaldehyde Schiff base flame retardant containing a hydroxyl group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of paperboard, in particular to a multi-layer composite waterproof and explosion-proof corrugated paperboard and a preparation method thereof. Background Art

[0002] With the progress of society and the popularization of environmental protection concepts, corrugated cardboard, as a multi-layer adhesive body, has a tendency to gradually replace wooden boxes in commodity packaging. It has high mechanical strength and can withstand certain collisions and falls during transportation. It is currently widely used in carton manufacturing and packaging of fragile goods.

[0003] However, the existing corrugated cardboard also has some shortcomings: it has no internal reinforcement structure and will break under the impact of strong external force, which limits the scope of use of corrugated cardboard. The existing corrugated cardboard is mostly made of fiber base paper, which has poor waterproof and flame retardancy. It is easy to damage the packaged items in humid, high temperature, open flame and other environments, causing great economic losses to people. Summary of the invention

[0004] The object of the present invention is to provide a multi-layer composite waterproof and burst-proof corrugated paperboard and a preparation method thereof, so as to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a multi-layer composite waterproof and burst-proof corrugated paperboard comprises the following steps:

[0007] S1: modified halloysite nanotubes, composite waterborne polyurethane, and cross-linked oxidized starch were used as flame retardant adhesives;

[0008] S2: using a flame retardant adhesive to sequentially bond the explosion-proof film layer, the foam board layer, the reinforcing fiber mesh layer, and the corrugated paperboard layer to obtain a corrugated paperboard;

[0009] S3: modified halloysite nanotubes and composite waterborne polyurethane as protective coating;

[0010] S4: coating the protective coating on the corrugated paperboard to form a protective layer, thereby obtaining a multi-layer composite waterproof and explosion-proof corrugated paperboard.

[0011] Furthermore, the explosion-proof film layer is a double-sided aluminum-plated PET film layer, and the foam board layer is a polystyrene foam board.

[0012] Furthermore, the reinforcing fiber mesh layer is composed of warp threads and weft threads interwoven together, the warp threads are basalt fiber threads, and the weft threads are one of basalt fiber threads, glass fiber threads, and carbon fiber threads.

[0013] Furthermore, the flame retardant adhesive comprises, by weight, 1-5 parts of modified halloysite nanotubes, 8-12 parts of composite waterborne polyurethane, and 32-48 parts of cross-linked oxidized starch.

[0014] Furthermore, the mass ratio of the modified halloysite nanotubes and the composite waterborne polyurethane in the protective coating is 8-12%.

[0015] Further, the preparation of cross-linked oxidized starch comprises the following steps:

[0016] Mix soluble starch and distilled water, adjust the pH to 2, heat to 55°C, add potassium permanganate, keep warm for 30-40 minutes, cool to 50°C, add glutaraldehyde, continue to keep warm for 1-2 hours, keep warm at 80-85°C for 44-48 hours, add isophorone diisocyanate, keep warm at 150°C for 10 hours, and obtain cross-linked oxidized starch.

[0017] Further, the preparation of modified halloysite nanotubes comprises the following steps:

[0018] (1) Anhydrous ethanol, acetone and 3-aminopropyltriethoxysilane are mixed, the pH is adjusted to 4.5-4.7, halloysite nanotubes are added, and the mixture is kept in a water bath at 78-82°C for 5-6 hours to obtain amino-modified halloysite nanotubes; the amino-modified halloysite nanotubes, graphene oxide and anhydrous ethanol are mixed, triethylamine is added, the mixture is heated to 118-122°C and kept in a water bath for 11-12 hours, the mixture is washed with anhydrous ethanol until neutral, dried and ball-milled to obtain composite halloysite nanotubes;

[0019] (2) mixing the composite halloysite nanotubes and deionized water, ultrasonically dispersing for 1-2 hours, adding acetic acid and L-aspartic acid, keeping the mixture at 60-70° C. for 5-6 hours, centrifuging, washing, and freeze-drying to obtain carboxylated composite halloysite nanotubes;

[0020] (3) A hydroxyl-containing salicylaldehyde Schiff base flame retardant and dimethyl sulfoxide are mixed, and a mixed solution of N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, dimethyl sulfoxide and carboxylated composite halloysite nanotubes is added, and the mixture is ultrasonically treated for 1-2 hours, kept at 45-55°C for 22-24 hours, filtered and washed with methanol for 3-5 times, and dried to obtain modified halloysite nanotubes.

[0021] Further, the preparation of the composite waterborne polyurethane comprises the following steps:

[0022] 1) Mix a hydroxyl-containing salicylaldehyde Schiff base flame retardant, a fluoroboric acid solution, and epoxy soybean oil, heat to 60-65°C and keep warm for 2-3 hours, add ethyl acetate, add saturated brine for extraction, dry, filter, and rotary evaporate to obtain a vegetable oil-based polyol;

[0023] 2) Under a nitrogen atmosphere, polypropylene glycol, vegetable oil-based polyol and hydroxyfluorosilicone oil are mixed, heated to 120°C and kept for 2 hours, cooled to 58-62°C, isophorone diisocyanate, diphenylmethane diisocyanate, ethylene glycol and dibutyltin dilaurate are added, heated to 78-82°C until the isocyanate content remains unchanged, cooled to 35-40°C, sodium ethylenediamine sulfonate and ethylenediamine are added, and deionized water is added for emulsification for 1-2 hours to obtain a composite waterborne polyurethane.

[0024] Furthermore, the preparation of a salicylaldehyde Schiff base flame retardant containing a hydroxyl group includes the following steps: mixing anhydrous ethanol, p-phenylenediamine, and salicylaldehyde, keeping warm at 82-85°C for 7-8 hours, adding DOPO, continuing to keep warm for 7-8 hours, cooling, centrifuging, washing, filtering, drying, and grinding to obtain a salicylaldehyde Schiff base flame retardant containing a hydroxyl group.

[0025] Beneficial effects of the present invention:

[0026] The invention provides a multi-layer composite waterproof and explosion-proof corrugated paperboard and a preparation method thereof. Through component and process design, an explosion-proof film layer, a foam board layer, a reinforcing fiber mesh layer and a corrugated paperboard layer are sequentially bonded with a green flame-retardant adhesive to obtain a corrugated paperboard. Modified halloysite nanotubes and composite water-based polyurethane are compounded as a protective coating and coated on the corrugated paperboard to obtain a green and environmentally friendly multi-layer composite waterproof and explosion-proof corrugated paperboard.

[0027] In order to improve the deformation resistance and burst resistance of the corrugated board in the present application, a tear-resistant reinforcing fiber mesh layer is introduced into the structure, wherein the reinforcing fiber mesh layer is composed of flame-retardant and high-temperature resistant warp and weft interwoven, thereby improving the mechanical strength of the corrugated board.

[0028] In order to meet the existing green development requirements, the present invention selects inexpensive, non-corrosive, and non-polluting starch adhesives as the base material of the flame retardant adhesive. In order to solve the shortcomings of natural starch adhesives such as poor bonding strength and poor water resistance, the present invention uses soluble starch as a raw material, oxidized starch is obtained by oxidation with potassium permanganate, and then cross-linked with glutaraldehyde and isophorone diisocyanate in two steps to obtain cross-linked oxidized starch, which is then compounded with a composite water-based polyurethane emulsion and modified halloysite nanotubes to obtain a flame retardant adhesive with good water resistance, high flame retardancy, and strong corrosion resistance;

[0029] The composite waterborne polyurethane emulsion is prepared by chemical grafting of vegetable oil-based polyol and polypropylene glycol as composite soft segments, isophorone diisocyanate and diphenylmethane diisocyanate as composite hard segments, and hydroxyl fluorosilicone oil as segment blocking agent; the vegetable oil-based polyol is a hydroxyl-containing salicylaldehyde Schiff base flame retardant ring-opened epoxidized soybean oil, and a phosphorus-containing Schiff base flame retardant group synthesized with salicylaldehyde, p-phenylenediamine and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) as raw materials is coupled to the side chain of vegetable oil fatty acid; flame retardant groups and fluorosilicone segments with low surface activity are introduced into the polyurethane segments, thereby realizing composite modification of waterborne polyurethane;

[0030] Halloysite nanotubes are introduced as fillers in flame retardant adhesives. In order to improve the uniformity of dispersion of halloysite nanotubes in flame retardant adhesives, the halloysite nanotubes are modified. First, their surface is aminated with 3-aminopropyltriethoxysilane, and then graphene oxide is loaded on their surface by electrostatic self-assembly to obtain hybrid flame retardant fillers, namely composite halloysite nanotubes, to improve their flame retardancy. Then, aspartic acid is used for modification to open the epoxy group of graphene oxide on the composite halloysite nanotubes and introduce carboxyl groups, thereby increasing the reaction sites of the composite halloysite nanotubes. Then, salicylaldehyde Schiff base flame retardant containing hydroxyl groups is reaction-grafted, thereby constructing a flame retardant filler containing P / N / Si multi-element organic-inorganic composites, thereby greatly improving their flame retardancy and fire extinguishing properties.

[0031] By controlling the ratio of modified halloysite nanotubes and composite waterborne polyurethane in the protective coating, the surface of the protective layer after drying has super hydrophobicity and flame retardancy, thereby extending the service life of the corrugated cardboard. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0034] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0035] Embodiment 1: A method for preparing a multi-layer composite waterproof and burst-proof corrugated paperboard, comprising the following steps:

[0036] S1: modified halloysite nanotubes, composite waterborne polyurethane, and cross-linked oxidized starch were used as flame retardant adhesives;

[0037] The flame retardant adhesive comprises, by weight, 1 part of modified halloysite nanotubes, 8 parts of composite waterborne polyurethane, and 32 parts of cross-linked oxidized starch;

[0038] The preparation of cross-linked oxidized starch comprises the following steps:

[0039] 2 g of soluble starch and 20 mL of distilled water were mixed, the pH was adjusted to 2, the temperature was raised to 55°C, 0.06 g of potassium permanganate was added, and the temperature was kept for 30 min, the temperature was lowered to 50°C, 4 mL of glutaraldehyde was added, and the temperature was kept for 1 h, and the temperature was kept at 80°C for 48 h, 2 mL of isophorone diisocyanate was added, and the temperature was kept at 150°C for 10 h to obtain cross-linked oxidized starch;

[0040] The preparation of the modified halloysite nanotubes comprises the following steps:

[0041] (1) 250 mL of anhydrous ethanol, 2.5 mL of acetone, and 0.01 mL of 3-aminopropyltriethoxysilane were mixed, the pH was adjusted to 4.5, 1 g of halloysite nanotubes were added, and the mixture was kept in a water bath at 78 °C for 6 h to obtain amino-modified halloysite nanotubes; 0.5 g of graphene oxide, 1 g of amino-modified halloysite nanotubes, and 200 mL of anhydrous ethanol were mixed, 3 mL of triethylamine was added, the mixture was heated to 118 °C and kept in a temperature range of 12 h, and the mixture was washed with anhydrous ethanol until neutral, dried, and ball-milled to obtain composite halloysite nanotubes;

[0042] (2) 1 g of composite halloysite nanotubes and 100 mL of deionized water were mixed, ultrasonically dispersed for 1 h, 20 mL of acetic acid and 1 g of L-aspartic acid were added, the mixture was kept at 60 °C for 6 h, centrifuged, washed, and freeze-dried to obtain carboxylated composite halloysite nanotubes;

[0043] (3) 2 g of a hydroxyl-containing salicylaldehyde Schiff base flame retardant and 20 mL of dimethyl sulfoxide were mixed, and a mixed solution of 1.6 g of N,N'-dicyclohexylcarbodiimide, 0.26 g of 4-dimethylaminopyridine, 40 mL of dimethyl sulfoxide and 1.6 g of carboxylated composite halloysite nanotubes was added, and the mixture was ultrasonically treated for 1 h, kept at 45 °C for 24 h, filtered and washed with methanol for 3 times, and dried to obtain modified halloysite nanotubes;

[0044] The preparation of the composite waterborne polyurethane comprises the following steps:

[0045] 1) Mix 5g of salicylaldehyde Schiff base flame retardant containing hydroxyl group, 5mg of fluoroboric acid solution and 4g of epoxy soybean oil, heat to 60℃ and keep warm for 3h, add 10mL of ethyl acetate, add 100mL of saturated brine to extract, dry, filter and rotary evaporate to obtain vegetable oil-based polyol;

[0046] 2) Under a nitrogen atmosphere, 3 g of polypropylene glycol, 7.2 g of vegetable oil-based polyol, and 4.1 g of hydroxyfluorosilicone oil were mixed, heated to 120 ° C for 2 h, cooled to 58 ° C, 8 g of isophorone diisocyanate, 8 g of diphenylmethane diisocyanate, 2 g of ethylene glycol, and 3 drops of dibutyltin dilaurate were added, the temperature was raised to 78 ° C until the isocyanate content remained unchanged, cooled to 35 ° C, 2 g of sodium ethylenediamine sulfonate and 1 g of ethylenediamine were added, and deionized water was added for emulsification for 1 h to obtain a composite waterborne polyurethane with a solid content of 40%;

[0047] The preparation of a salicylaldehyde Schiff base flame retardant containing a hydroxyl group comprises the following steps: 150 mL of anhydrous ethanol, 1.08 g of p-phenylenediamine, and 2.13 mL of salicylaldehyde are mixed, the mixture is kept warm at 82° C. for 8 hours, 4.32 g of DOPO is added, the mixture is kept warm for 7 hours, and the mixture is cooled, centrifuged, washed, filtered, dried, and ground to obtain a salicylaldehyde Schiff base flame retardant containing a hydroxyl group;

[0048] S2: using a flame retardant adhesive to sequentially bond the explosion-proof film layer, the foam board layer, the reinforcing fiber mesh layer, and the corrugated paperboard layer to obtain a corrugated paperboard;

[0049] The explosion-proof film layer is a double-sided aluminum-plated PET film layer; the foam board layer is a polystyrene foam board; the reinforcing fiber mesh layer is composed of warp and weft interwoven, the warp is a basalt fiber line, and the weft is a glass fiber line; the warp density is 200 strands / 10cm, and the weft density is 180 strands / 10cm;

[0050] S3: modified halloysite nanotubes and composite waterborne polyurethane as protective coating;

[0051] The mass ratio of modified halloysite nanotubes and composite waterborne polyurethane in the protective coating is 8%;

[0052] S4: coating the protective coating on the corrugated paperboard to form a protective layer, thereby obtaining a multi-layer composite waterproof and explosion-proof corrugated paperboard.

[0053] Embodiment 2: A method for preparing a multi-layer composite waterproof and burst-proof corrugated paperboard, comprising the following steps:

[0054] S1: modified halloysite nanotubes, composite waterborne polyurethane, and cross-linked oxidized starch were used as flame retardant adhesives;

[0055] The flame retardant adhesive is composed of 3 parts of modified halloysite nanotubes, 10 parts of composite waterborne polyurethane, and 42 parts of cross-linked oxidized starch in parts by mass.

[0056] The preparation of cross-linked oxidized starch comprises the following steps:

[0057] 2 g of soluble starch and 20 mL of distilled water were mixed, the pH was adjusted to 2, the temperature was raised to 55°C, 0.06 g of potassium permanganate was added, and the temperature was kept for 35 min, the temperature was lowered to 50°C, 4 mL of glutaraldehyde was added, and the temperature was kept for 1.5 h, and the temperature was kept at 83°C for 46 h, 2 mL of isophorone diisocyanate was added, and the temperature was kept at 150°C for 10 h to obtain cross-linked oxidized starch;

[0058] The preparation of the modified halloysite nanotubes comprises the following steps:

[0059] (1) 250 mL of anhydrous ethanol, 2.5 mL of acetone, and 0.01 mL of 3-aminopropyltriethoxysilane were mixed, the pH was adjusted to 4.6, 1 g of halloysite nanotubes were added, and the mixture was kept in a water bath at 80 °C for 5.5 h to obtain amino-modified halloysite nanotubes; 0.5 g of graphene oxide, 1 g of amino-modified halloysite nanotubes, and 200 mL of anhydrous ethanol were mixed, 3 mL of triethylamine was added, the mixture was heated to 120 °C and kept in a temperature range of 11.5 h, and the mixture was washed with anhydrous ethanol until neutral, dried, and ball-milled to obtain composite halloysite nanotubes;

[0060] (2) 1 g of composite halloysite nanotubes and 100 mL of deionized water were mixed, ultrasonically dispersed for 1.5 h, 20 mL of acetic acid and 1 g of L-aspartic acid were added, and the mixture was kept at 65 °C for 5.5 h, centrifuged, washed, and freeze-dried to obtain carboxylated composite halloysite nanotubes;

[0061] (3) 2 g of a hydroxyl-containing salicylaldehyde Schiff base flame retardant and 20 mL of dimethyl sulfoxide were mixed, and a mixed solution of 1.6 g of N,N'-dicyclohexylcarbodiimide, 0.26 g of 4-dimethylaminopyridine, 40 mL of dimethyl sulfoxide and 1.6 g of carboxylated composite halloysite nanotubes was added, and the mixture was ultrasonically treated for 1.5 h, kept at 50 °C for 23 h, filtered and washed with methanol for 4 times, and dried to obtain modified halloysite nanotubes;

[0062] The preparation of the composite waterborne polyurethane comprises the following steps:

[0063] 1) Mix 5g of salicylaldehyde Schiff base flame retardant containing hydroxyl group, 5mg of fluoroboric acid solution and 4g of epoxidized soybean oil, heat to 62℃ and keep warm for 2.5h, add 10mL of ethyl acetate, add 100mL of saturated brine to extract, dry, filter and rotary evaporate to obtain vegetable oil-based polyol;

[0064] 2) Under a nitrogen atmosphere, 3 g of polypropylene glycol, 7.2 g of vegetable oil-based polyol, and 4.1 g of hydroxyfluorosilicone oil were mixed, heated to 120 ° C for 2 h, cooled to 60 ° C, 8 g of isophorone diisocyanate, 8 g of diphenylmethane diisocyanate, 2 g of ethylene glycol, and 3 drops of dibutyltin dilaurate were added, the temperature was raised to 80 ° C until the isocyanate content remained unchanged, cooled to 38 ° C, 2 g of sodium ethylenediamine sulfonate and 1 g of ethylenediamine were added, and deionized water was added for emulsification for 1.5 h to obtain a composite waterborne polyurethane with a solid content of 40%;

[0065] The preparation of a salicylaldehyde Schiff base flame retardant containing a hydroxyl group comprises the following steps: 150 mL of anhydrous ethanol, 1.08 g of p-phenylenediamine, and 2.13 mL of salicylaldehyde are mixed, the mixture is kept warm at 83° C. for 7.5 hours, 4.32 g of DOPO is added, the mixture is kept warm for another 7.5 hours, and the mixture is cooled, centrifuged, washed, filtered, dried, and ground to obtain a salicylaldehyde Schiff base flame retardant containing a hydroxyl group;

[0066] S2: using a flame retardant adhesive to sequentially bond the explosion-proof film layer, the foam board layer, the reinforcing fiber mesh layer, and the corrugated paperboard layer to obtain a corrugated paperboard;

[0067] The explosion-proof film layer is a double-sided aluminum-plated PET film layer; the foam board layer is a polystyrene foam board; the reinforcing fiber mesh layer is composed of warp and weft interwoven, the warp is a basalt fiber line, and the weft is a glass fiber line; the warp density is 200 strands / 10cm, and the weft density is 180 strands / 10cm;

[0068] S3: modified halloysite nanotubes and composite waterborne polyurethane as protective coating;

[0069] The mass ratio of modified halloysite nanotubes and composite waterborne polyurethane in the protective coating is 10%;

[0070] S4: coating the protective coating on the corrugated paperboard to form a protective layer, thereby obtaining a multi-layer composite waterproof and explosion-proof corrugated paperboard.

[0071] Embodiment 3: A method for preparing a multi-layer composite waterproof and burst-proof corrugated paperboard, comprising the following steps:

[0072] S1: modified halloysite nanotubes, composite waterborne polyurethane, and cross-linked oxidized starch were used as flame retardant adhesives;

[0073] The flame retardant adhesive comprises, by weight, 5 parts of modified halloysite nanotubes, 12 parts of composite waterborne polyurethane, and 48 parts of cross-linked oxidized starch;

[0074] The preparation of cross-linked oxidized starch comprises the following steps:

[0075] 2 g of soluble starch and 20 mL of distilled water were mixed, the pH was adjusted to 2, the temperature was raised to 55°C, 0.06 g of potassium permanganate was added, and the temperature was kept for 40 min, the temperature was lowered to 50°C, 4 mL of glutaraldehyde was added, and the temperature was kept for 2 h, the temperature was kept at 85°C for 44 h, 2 mL of isophorone diisocyanate was added, and the temperature was kept at 150°C for 10 h to obtain cross-linked oxidized starch;

[0076] The preparation of the modified halloysite nanotubes comprises the following steps:

[0077] (1) 250 mL of anhydrous ethanol, 2.5 mL of acetone, and 0.01 mL of 3-aminopropyltriethoxysilane were mixed, the pH was adjusted to 4.7, 1 g of halloysite nanotubes were added, and the mixture was kept in a water bath at 82 °C for 5 h to obtain amino-modified halloysite nanotubes; 0.5 g of graphene oxide, 1 g of amino-modified halloysite nanotubes, and 200 mL of anhydrous ethanol were mixed, 3 mL of triethylamine was added, the mixture was heated to 122 °C and kept in a temperature range of 11 h, and the mixture was washed with anhydrous ethanol until neutral, dried, and ball-milled to obtain composite halloysite nanotubes;

[0078] (2) 1 g of composite halloysite nanotubes and 100 mL of deionized water were mixed, ultrasonically dispersed for 2 h, 20 mL of acetic acid and 1 g of L-aspartic acid were added, and the mixture was kept at 70 °C for 5 h, centrifuged, washed, and freeze-dried to obtain carboxylated composite halloysite nanotubes;

[0079] (3) 2 g of a hydroxyl-containing salicylaldehyde Schiff base flame retardant and 20 mL of dimethyl sulfoxide were mixed, and a mixed solution of 1.6 g of N,N'-dicyclohexylcarbodiimide, 0.26 g of 4-dimethylaminopyridine, 40 mL of dimethyl sulfoxide and 1.6 g of carboxylated composite halloysite nanotubes was added, and the mixture was ultrasonically treated for 2 h, kept at 55 °C for 22 h, filtered and washed with methanol for 5 times, and dried to obtain modified halloysite nanotubes;

[0080] The preparation of the composite waterborne polyurethane comprises the following steps:

[0081] 1) Mix 5g of salicylaldehyde Schiff base flame retardant containing hydroxyl group, 5mg of fluoroboric acid solution and 4g of epoxy soybean oil, heat to 65℃ and keep warm for 2h, add 10mL of ethyl acetate, add 100mL of saturated brine to extract, dry, filter and rotary evaporate to obtain vegetable oil-based polyol;

[0082] 2) Under a nitrogen atmosphere, 3 g of polypropylene glycol, 7.2 g of vegetable oil-based polyol, and 4.1 g of hydroxyfluorosilicone oil were mixed, heated to 120 ° C and kept for 2 h, cooled to 62 ° C, 8 g of isophorone diisocyanate, 8 g of diphenylmethane diisocyanate, 2 g of ethylene glycol, and 3 drops of dibutyltin dilaurate were added, and the temperature was raised to 82 ° C until the isocyanate content remained unchanged, cooled to 40 ° C, 2 g of sodium ethylenediamine sulfonate and 1 g of ethylenediamine were added, and deionized water was added for emulsification for 2 h to obtain a composite waterborne polyurethane with a solid content of 40%;

[0083] The preparation of a salicylaldehyde Schiff base flame retardant containing a hydroxyl group comprises the following steps: 150 mL of anhydrous ethanol, 1.08 g of p-phenylenediamine, and 2.13 mL of salicylaldehyde are mixed, the mixture is kept warm at 85° C. for 7 hours, 4.32 g of DOPO is added, the mixture is kept warm for 8 hours, and the mixture is cooled, centrifuged, washed, filtered, dried, and ground to obtain a salicylaldehyde Schiff base flame retardant containing a hydroxyl group;

[0084] S2: using a flame retardant adhesive to sequentially bond the explosion-proof film layer, the foam board layer, the reinforcing fiber mesh layer, and the corrugated paperboard layer to obtain a corrugated paperboard;

[0085] The explosion-proof film layer is a double-sided aluminum-plated PET film layer; the foam board layer is a polystyrene foam board; the reinforcing fiber mesh layer is composed of warp and weft interwoven, the warp is a basalt fiber line, and the weft is a glass fiber line; the warp density is 200 strands / 10cm, and the weft density is 180 strands / 10cm;

[0086] S3: modified halloysite nanotubes and composite waterborne polyurethane as protective coating;

[0087] The mass ratio of modified halloysite nanotubes and composite waterborne polyurethane in the protective coating is 12%;

[0088] S4: coating the protective coating on the corrugated paperboard to form a protective layer, thereby obtaining a multi-layer composite waterproof and explosion-proof corrugated paperboard.

[0089] Comparative Example 1: Taking Example 3 as the control group, the modified halloysite nanotubes were replaced by halloysite nanotubes, and the other processes were normal.

[0090] Comparative Example 2: Taking Example 3 as the control group, the composite water-based polyurethane was replaced with water-based polyurethane (BZ-7: Changzhou Baichang Coatings Technology Co., Ltd.), and the other processes were normal.

[0091] Comparative Example 3: Example 3 was used as a control group, but no salicylaldehyde Schiff base flame retardant containing hydroxyl groups was prepared, and other processes were normal.

[0092] The single-sided coating amount of the flame retardant adhesive in the examples and comparative examples is 250 g / m 2 , the thickness of the protective layer is 200µm.

[0093] Source of raw materials (for demonstration only):

[0094] Double-sided aluminum-plated PET film layer 9506063: Forsman Technology (Beijing) Co., Ltd.; foam board layer is polystyrene foam board (20mm) 0021: Hebei Jiejia Energy Saving Technology Co., Ltd.; basalt fiber line S-X1235: Dongguan Shengxin Special Rope Co., Ltd.; glass fiber line 50 / 4: Renqiu Tainuo Fiberglass Products Factory; corrugated cardboard (7-layer EBA corrugated cardboard) (thickness 8mm): Anhui Nian Delao Paper Packaging Technology Co., Ltd.; hydroxy fluorosilicone oil: Wuhan Rongcan Biotechnology Co., Ltd.; diphenylmethane diisocyanate jxyb0198: Wuhan Jixin Yibang Biotechnology Co., Ltd.; sodium ethylenediamine sulfonate 34730-59-1: Hubei Chushengwei Chemical Co., Ltd.; soluble starch S104452, glutaraldehyde G105905, 3-aminopropyl triethoxysilane A107147, halloysite nanotube H431 905, graphene oxide G466617, triethylamine T103285, L-aspartic acid S432943, dimethyl sulfoxide D670381, N,N'-dicyclohexylcarbodiimide N420184, 4-dimethylaminopyridine D109207, fluoroboric acid solution F291750, epoxidized soybean oil E107074, polypropylene glycol P103210, isophorone diisocyanate I109582 , ethylene glycol E103319, dibutyltin dilaurate D100274, ethylenediamine E112132, p-phenylenediamine P108424, salicylaldehyde S103742, DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) D102416: Aladdin reagent; potassium permanganate, anhydrous ethanol, acetone, acetic acid, methanol, ethyl acetate, methanol, analytical grade: Sinopharm Group reagent.

[0095] Performance test: The corrugated paperboards prepared in the embodiments and comparative examples were subjected to performance tests;

[0096] Burst strength: Test the burst strength with reference to GB / T6544-2008; Hydrophobicity: Test the water contact angle with a contact angle meter, using a 3µL deionized water droplet; Flame retardancy: Perform a UL-94 vertical combustion test, using a vertical combustion instrument to test the flame retardancy of the material, place the test sample vertically in the instrument fixture, and the propane fire source automatically moves to the bottom of the sample for 10 seconds to ignite; the specific data is shown in Table 1;

[0097] Table 1

[0098]

[0099] By comparing Example 3 with Comparative Example 1 and Comparative Example 3, it can be seen that the halloysite nanotubes are modified by first amminating their surface with 3-aminopropyltriethoxysilane, and then loading graphene oxide on their surface by electrostatic self-assembly to obtain a hybrid flame retardant filler, namely, composite halloysite nanotubes, to improve their flame retardancy, and then modifying them with aspartic acid to open the epoxy group of graphene oxide on the composite halloysite nanotubes and introduce carboxyl groups, thereby increasing the reaction sites of the composite halloysite nanotubes, and then reaction-grafting a salicylaldehyde Schiff base flame retardant containing a hydroxyl group, thereby constructing a flame retardant filler containing a P / N / Si multi-element organic-inorganic composite, thereby greatly improving its flame retardancy, fire extinguishing properties and water resistance.

[0100] By comparing Example 3 with Comparative Examples 2 and 3, it can be seen that the composite waterborne polyurethane emulsion is prepared by a chemical grafting method using vegetable oil-based polyols and polypropylene glycol as a composite soft segment, isophorone diisocyanate and diphenylmethane diisocyanate as a composite hard segment, and hydroxyl fluorosilicone oil as a segment blocking agent; the vegetable oil-based polyol is a hydroxyl-containing salicylaldehyde Schiff base flame retardant ring-opened epoxy soybean oil, and a phosphorus-containing Schiff base flame retardant group synthesized using salicylaldehyde, p-phenylenediamine, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) as raw materials is coupled to the vegetable oil fatty acid side chain; a flame retardant group is introduced into the main chain, and a fluorosilicone segment with low surface activity is introduced into the side chain, thereby achieving composite modification of the waterborne polyurethane, thereby improving the water resistance and flame retardancy of the corrugated board.

[0101] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a multi-layer composite waterproof and explosion-proof corrugated paperboard, characterized in that: The following steps are involved: S1: modified halloysite nanotubes, composite waterborne polyurethane, and cross-linked oxidized starch were used as flame retardant adhesives; S2: using a flame retardant adhesive to sequentially bond the explosion-proof film layer, the foam board layer, the reinforcing fiber mesh layer, and the corrugated paperboard layer to obtain a corrugated paperboard; S3: modified halloysite nanotubes and composite waterborne polyurethane as protective coating; S4: coating the protective coating on the corrugated paperboard to form a protective layer, thereby obtaining a multi-layer composite waterproof and explosion-proof corrugated paperboard; The preparation of the modified halloysite nanotubes comprises the following steps: (1) Anhydrous ethanol, acetone and 3-aminopropyltriethoxysilane are mixed, the pH is adjusted to 4.5-4.7, halloysite nanotubes are added, and the mixture is kept in a water bath at 78-82°C for 5-6 hours to obtain amino-modified halloysite nanotubes; the amino-modified halloysite nanotubes, graphene oxide and anhydrous ethanol are mixed, triethylamine is added, the mixture is heated to 118-122°C and kept in a water bath for 11-12 hours, the mixture is washed with anhydrous ethanol until neutral, dried and ball-milled to obtain composite halloysite nanotubes; (2) mixing the composite halloysite nanotubes and deionized water, ultrasonically dispersing for 1-2 hours, adding acetic acid and L-aspartic acid, keeping the mixture at 60-70° C. for 5-6 hours, centrifuging, washing, and freeze-drying to obtain carboxylated composite halloysite nanotubes; (3) Mixing a hydroxyl-containing salicylaldehyde Schiff base flame retardant and dimethyl sulfoxide, adding a mixed solution of N,N'-dicyclohexylcarbodiimide, 4-dimethylaminopyridine, dimethyl sulfoxide, and carboxylated composite halloysite nanotubes, ultrasonically treating for 1-2 hours, keeping warm at 45-55°C for 22-24 hours, filtering and washing with methanol for 3-5 times, and drying to obtain modified halloysite nanotubes; The preparation of the composite waterborne polyurethane comprises the following steps: 1) Mix a hydroxyl-containing salicylaldehyde Schiff base flame retardant, a fluoroboric acid solution, and epoxy soybean oil, heat to 60-65°C and keep warm for 2-3 hours, add ethyl acetate, add saturated brine for extraction, dry, filter, and rotary evaporate to obtain a vegetable oil-based polyol; 2) In a nitrogen atmosphere, polypropylene glycol, vegetable oil-based polyol, and hydroxy fluorosilicone oil are mixed, heated to 120°C and kept for 2 hours, cooled to 58-62°C, isophorone diisocyanate, diphenylmethane diisocyanate, ethylene glycol, and dibutyltin dilaurate are added, heated to 78-82°C until the isocyanate content remains unchanged, cooled to 35-40°C, sodium ethylenediamine sulfonate and ethylenediamine are added, and deionized water is added for emulsification for 1-2 hours to obtain a composite waterborne polyurethane; The preparation of the salicylaldehyde Schiff base flame retardant containing hydroxyl comprises the following steps: mixing anhydrous ethanol, p-phenylenediamine and salicylaldehyde, keeping the mixture at 82-85° C. for 7-8 hours, adding DOPO, keeping the mixture at 82-85° C. for 7-8 hours, cooling, centrifuging, washing, filtering, drying and grinding to obtain the salicylaldehyde Schiff base flame retardant containing hydroxyl; The flame retardant adhesive comprises, by weight, 1-5 parts of modified halloysite nanotubes, 8-12 parts of composite waterborne polyurethane, and 32-48 parts of cross-linked oxidized starch.

2. The method for preparing a multi-layer composite waterproof and explosion-proof corrugated paperboard according to claim 1, characterized in that: The explosion-proof film layer is a double-sided aluminum-plated PET film layer, and the foam board layer is a polystyrene foam board.

3. The method for preparing a multi-layer composite waterproof and explosion-proof corrugated paperboard according to claim 1, characterized in that: The reinforcing fiber mesh layer is composed of warp threads and weft threads interwoven together, wherein the warp threads are basalt fiber threads, and the weft threads are one of basalt fiber threads, glass fiber threads, and carbon fiber threads.

4. The method for preparing a multi-layer composite waterproof and explosion-proof corrugated paperboard according to claim 1, characterized in that: The mass ratio of the modified halloysite nanotubes and the composite waterborne polyurethane in the protective coating is 8-12%.

5. The method for preparing a multi-layer composite waterproof and explosion-proof corrugated paperboard according to claim 1, characterized in that: The preparation of the cross-linked oxidized starch comprises the following steps: Mix soluble starch and distilled water, adjust the pH to 2, heat to 55°C, add potassium permanganate, keep warm for 30-40 minutes, cool to 50°C, add glutaraldehyde, continue to keep warm for 1-2 hours, keep warm at 80-85°C for 44-48 hours, add isophorone diisocyanate, keep warm at 150°C for 10 hours, and obtain cross-linked oxidized starch.

6. A multi-layer composite waterproof and explosion-proof corrugated paperboard, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method of fluorinated halloysite nanotube / waterborne polyurethane composite hydrophobic coating layer

    CN108977030A

  • Adhesive for plywood

    CN109233687A

  • Packaging box for electronic product transportation

    CN214058213U